Learning Based On Flipped Techniques Among The Technical Students With Different Learning Styles - Azyani A. Jalil, Noor; Iman Kassim, Nurul; Rizal Madar, Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
Flipped learning is a relatively new method of learning in the Malaysian education system. This is because the percentage of usage is still not satisfactory. This method of learning is to use active learning concepts where students are exposed to several activities in the classroom to help students understand the learning and indirectly enhance their academic achievement. This study used the Quasi-Experimental method and this study involved 74 students from two polytechnics in Malaysia and were selected using purposive sampling method. For the control group, their learning used traditional methods whereby they would carry out their teaching and learning process as usual while the treatment group would carry out the teaching and learning process using flipped learning. The findings show that a total of 41 students had visual inputs compared to 33 verbal inputs. Besides, there was a 97.2% increase in academic achievement among students using flipped learning methods compared to students who followed conventional learning. The mean of students in the treatment group who used visual input as a medium in their learning was more likely to increase by 45.68 than for students who used the 35.91 auditory medium. On the whole, students who follow flipped learning methods can improve their academic achievement. The conclusion can be made that, by designing appropriate learning methods for students, this can help them overcome problems in learning and indirectly help educators in the process of delivering knowledge.